2014
DOI: 10.1185/03007995.2014.924913
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent sexual activity and cancer risk: physicians’ duty to inform?

Abstract: Yearly, 33,000 cancer diagnoses in the US are attributed to human papillomavirus (HPV), with cervical cancer the most common. HPV is transmitted through sexual contact; HPV types 16 and 18 cause the majority of ano-genital cancers in men and women. HPV causes ∼100% of cervical cancers, ∼90% of anal cancers, and ∼50% of vaginal, vulvar, and penile cancers. HPV is also involved in ∼70% of oropharyngeal cancers (OPCs) in the US. The CDC recommends routine administration to all female (bivalent or quadrivalent vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…These behaviours, which include smoking, heavy alcohol consumption and drug use, have all been shown to contribute to excess morbidity and mortality during adulthood [7]. Furthermore, it has been identified that tobacco, alcohol and drug use [8, 9] and sexual risk taking behaviour [9, 10] are two of the major causes of death and illness among adolescents and young adults. It is thus important to understand trends in health inequalities and the underlying social determinants of these in order to develop interventions and policies to reduce the effects of these upon population health [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…These behaviours, which include smoking, heavy alcohol consumption and drug use, have all been shown to contribute to excess morbidity and mortality during adulthood [7]. Furthermore, it has been identified that tobacco, alcohol and drug use [8, 9] and sexual risk taking behaviour [9, 10] are two of the major causes of death and illness among adolescents and young adults. It is thus important to understand trends in health inequalities and the underlying social determinants of these in order to develop interventions and policies to reduce the effects of these upon population health [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these behaviours contribute to the leading causes of mortality and morbidity among adolescents, such as suicide attempts, injuries and the various risks associated with unprotected sexual behaviour, conditions related to tobacco or alcohol use and overweight or obesity [3–5]. The majority of adolescent death and illness are caused by risk behaviours that can be grouped into four categories: tobacco, alcohol and drug use; dietary behaviours; physical activity; and sexual behaviours [6, 7]. These key health-risk behaviours are often the focus of prevention strategies for non-communicable diseases and some sexual conditions [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…These missed opportunities have also been implicated in the slow uptake of the human papilloma virus (HPV) vaccine among those who could most benefit from it. Clinicians who do not feel competent or comfortable discussing sexual matters often find it difficult to bring up the importance of the HPV vaccine and it is, therefore, neither discussed nor provided (Centers for Disease Control and Prevention, 2013;Quinn, Vadaparampil, Johns, Alexander, & Giuliano, 2014).…”
Section: The Need For a Sexual Health Focusmentioning
confidence: 99%